Properties and Utilization of Fly Ash for Treating Acid Mine Drainage - Nurlela; Agustina, Tuty Emilia; Arita, Susila; Bahrin, David; Fatimura, Muhrinsyah; Masriatini, Rully; Gayatri, Rianyza (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2025)
The combustion of coal in power plants (PLTU) generates fly ash containing silica dioxide (SiO?) and alumina (Al?O?), which exhibit promising properties as adsorptive materials. Fly ash, typically regarded as an industrial by-product, has been widely explored for its application as an adsorbent in wastewater purification. One of the most challenging wastewaters is acid mine drainage, characterized by strong acidity (pH < 5), residual contaminants, and elevated concentrations of heavy metal ions such as manganese (Mn) and iron (Fe). When released untreated, this effluent poses significant risks to both surface and groundwater quality in mining areas. This study focuses on the characterization and utilization of fly ash as an adsorbent to neutralize acidity and reduce Mn and Fe concentrations in acid mine drainage. The material was characterized using SEM-EDX and XRD techniques, followed by adsorption experiments. To enhance its properties, fly ash underwent physical activation through heating at 100 °C for 60 minutes. The activation process modified its structure, expanding pore volume and increasing surface area, thereby improving adsorption performance. The experimental results revealed significant differences in the properties of fly ash before and after activation. Activated fly ash effectively raised the pH of acid mine drainage to near-neutral conditions while achieving removal efficiencies of 96.61% for Mn and 83.33% for Fe using 50 g of adsorbent. These findings highlight the potential of fly ash as a low-cost and effective material for acid mine drainage treatment, both for acidity control and heavy metal removal.